Predominance and effect of graduation belt on rapid weight loss in Brazilian Jiu-jitsu athletes - De Albuquerque Mauricio, C.; Fraga Vilardo, I. D.; Goncalves, A. F.; Pereira Azevedo Teixeira, R.; Valenzuela Perez, D. I.; Brito, C. J.; Merino-Munoz, P.; Miarka, B. (Journal of Physical Education and Sport, 2023)
Combat sports such as judo, kickboxing, boxing, wrestling, Brazilian jiu-jitsu (BJJ), taekwondo, and karate are sports in which two individuals compete. Weight divisions were created to avoid possible injuries that can happen by differences in strength due to a significant disparity in body mass, as well as to implement a more balanced and fair competition environment between opponents. BJJ differs from the way of weighing in other combat sports modalities concerning the interval between weigh-in and first fight, approximately 10 minutes. The present study aimed to verify if the belt rank of jiu-jitsu competitors impacts weight loss and how weight is lost. Methodology: This is an observational study with 162 national athletes (67.7% men and 38.38% black belts), with 34.5 (6.8) years of practice in Brazilian jiu-jitsu, who participated in national competitions in Brazil between June and August 2021. They answered a questionnaire about their weight history and impacts on mass body gain. The frequency and percentage of responses were analyzed, in addition to the performance of the Kruskal-Wallis graduation tests, to compare RWL and methods and perception factors during PPR. Our results demonstrated that 135 athletes, 80% men and 38% black belts, with an average age of 29.5 years and an average practice time of 7.5 years. 62% of athletes reported doing PPR with a 3.9% decrease in body mass up to 10 days before the competition. Black belt athletes reported doing PPR more frequently (69%) and lost more body mass than the other graduations (4.6%). In addition, brown and black belts reported feeling more fatigued during PPR. The graduation and time of BJJ practice seem to influence the performance of RWL (4.6%) for weight loss to compete, with black belt athletes performing it more commonly; however, there are possible discomforts such as dizziness, fatigue, and cramps.